Ascertaining the Francophone population in Ontario: validating the language variable in health data - Batista, Ricardo; Hsu, Amy T.; Bouchard, Louise; Reaume, Michael; Rhodes, Emily; Sucha, Ewa; Guerin, Eva; Prud'homme, Denis; Manuel, Douglas G.; Tanuseputro, Peter (BMC Medical Research Methodology, 2024)
Abstract Background Language barriers can impact health care and outcomes. Valid and reliable language data is central to studying health inequalities in linguistic minorities. In Canada, language variables are available in administrative health databases; however, the validity of these variables has not been studied. This study assessed concordance between language variables from administrative health databases and language variables from the Canadian Community Health Survey (CCHS) to identify Francophones in Ontario.

Les données linguistiques pour la recherche et la planification en santé : possibilité et limites pour l'étude des francophones en situation minoritaire - Bouchard, Louise; Lizotte, Mathieu (Minorités linguistiques et société, 2024)
Malgré de remarquables avancées de recherche sur la problématique de la santé en contexte francophone minoritaire, la disponibilité de variables linguistiques complètes et cohérentes dans les bases de données nationales de santé demeure lacunaire et fragmentée, constituant un défi considérable pour l’étude de la santé des membres des communautés francophones en situation minoritaire (CFSM) et la planification de services adaptés à cette population dispersée. Cet article offre un bilan exhaustif des possibilités et des limites des données disponibles permettant l’étude de la santé des CFSM. Ce faisant, il met en lumière une série de problèmes méthodologiques, dont le manque de données pertinentes, l’absence de variables standardisées et les faibles effectifs pour l’analyse régionale, entre autres. Ces lacunes entravent considérablement la capacité des chercheuses et chercheurs à étudier les conditions et les besoins spécifiques des CFSM en ce qui concerne la santé et la planification de la santé. Mots-clés : données linguistiques, problèmes méthodologiques, francophone, minorité, quantification

Enquête exploratoire sur le recueil de la variable linguistique dans les données administratives des hôpitaux de la région du RLISS-Champlain - Chomienne, Marie-Hélène; LeClerc, Chantale; Schnarch, Brian; Bouchard, Louise; McKay, Martine; Farmanova, Elina (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, Réseau local d’intégration des services de santé de Champlain, 2011)

La mobilisation des connaissances en santé dans les CFSM [infographie] - Consortium national de formation en santé (2021)

La santé des francophones en situation minoritaire : un urgent besoin de plus d’information pour offrir de meilleurs services - Consortium national de formation en santé; Société Santé en français (La santé des francophones en situation minoritaire : un urgent besoin de plus d’information pour offrir de meilleurs services, 2010)

Equity, safety & health outcomes: The case for a national minimum data standard around health workforce language data in Canada - Demers, Chantale; Richard, Lise; Bourgeault, Ivy. Lynn

Qui sont les francophones ? Analyse des définitions selon les variables du recensement de 2001 - Forgues, Éric; Landry, Rodrigue; Boudreau, Jonathan (Institut canadien de recherche sur les minorités linguistiques et Consortium national de formation en santé, 2009)

Les données administratives et d’enquêtes sur l’état de santé et l’accès aux services des communautés francophones en situation minoritaire : potentiel d’analyse et état de situation. Rapport - Gaboury, Isabelle; Guignard Noël, Josée; Forgues, Éric; Bouchard, Louise (Consortium national de formation en santé, 2009)

Populations de langue officielle en situation minoritaire selon différentes méthodes de dénombrement. Rapport - Guignard Noël, Josée; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2020)

Qui sont les francophones ? Analyse des définitions selon les variables du recensement. Mise à jour : recensement de 2011 - Guignard-Noël, Josée; Forgues, Éric; Landry, Rodrigue (Institut canadien de recherche sur les minorités linguistiques, 2014)

Comment inclure la variable linguistique dans la demande de subvention [infographie] - Institut du Savoir Montfort; Unité de soutien de la SRAP en Ontario

La mobilisation des connaissances en santé dans les petites communautés francophones en situation minoritaire. Ses défis, ses conditions de succès - Johnson, Marc. L.; Cimon, Virginie; Dancause, Luc; Forest, Mariève (SOCIUS recherche et conseils, 2021)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°001) - Lafrenière, Sylvie (Statistics Canada, 2009)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°2) - Lafrenière, Sylvie (Statistics Canada, 2013)

Methodological issues in analysing small populations using CCHS cycles based on the official language minority studies - Makvandi, Ewa; Bouchard, Louise; Bergeron, Pierre-Jerôme; Sedigh, Golnaz (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Statistical analyses for small populations or small domains of interest can be challenging. To obtain reliable estimates, only very large surveys such as the Canadian Community Health Survey can be considered. However, despite its good geographical and temporal coverage, the analysis of small populations in smaller regions (e.g., health regions) and in regards to specific health issues remains challenging. We will look at the methodological issues in analysis of small populations in relation to sampling and non-sampling survey errors that affect the precision and accuracy of the estimates. Francophone minorities in Canada will be used to illustrate the issues throughout the paper.

Comparison of sampling methods for hard-to-reach Francophone populations: Yield and adequacy of advertisement and respondent-driven sampling - Ngwakongnwi, Emmanuel; King-Shier, athryn. M.; Hemmelgarn, Brenda. R.; Musto, Richard; Quan, Hude (Open medicine, 2014)
Francophones who live outside the primarily French-speaking province of Quebec, Canada, risk being excluded from research by lack of a sampling frame. We examined the adequacy of random sampling, advertising, and respondent-driven sampling for recruitment of francophones for survey research. Methods: We recruited francophones residing in the city of Calgary, Alberta, through advertising and respondentdriven sampling. These 2 samples were then compared with a random subsample of Calgary francophones derived from the 2006 Canadian Community Health Survey (CCHS). We assessed the effectiveness of advertising and respondent-driven sampling in relation to the CCHS sample by comparing demographic characteristics and selected items from the CCHS (specifically self-reported general health status, perceived weight, and having a family doctor). Results: We recruited 120 francophones through advertising and 145 through respondent-driven sampling; the random sample from the CCHS consisted of 259 records. The samples derived from advertising and respondentdriven sampling differed from the CCHS in terms of age (mean ages 41.0, 37.6, and 42.5 years, respectively), sex (proportion of males 26.1%, 40.6%, and 56.6%, respectively), education (college or higher 86.7% , 77.9% , and 59.1%, respectively), place of birth (immigrants accounting for 45.8%, 55.2%, and 3.7%, respectively), and not having a regular medical doctor (16.7%, 34.5%, and 16.6%, respectively). Differences were not tested statistically because of limitations on the analysis of CCHS data imposed by Statistics Canada. Interpretation: The samples generated exclusively through advertising and respondent-driven sampling were not representative of the gold standard sample from the CCHS. Use of such biased samples for research studies could generate misleading results.

The new Inclusive definition of Francophone (IDF) - Office of Francophone Affairs (2020)

Énoncé de position commune sur la variable linguistique - Regroupement des Entités de planification des services de santé en français de l’Ontario (Réseau des services de santé en français de l’Est de l’Ontario, 2013)

Better data for better planning: The challenge of evidence-based data for sound planning of French-Language health services in Ontario - Réseau des services de santé en français de l’Est de l’Ontario (The challenge of evidence-based data for sound planning of French-Language health services in Ontario, 2013)

Des données pour mieux planifier: Le défi des données pertinentes pour une planification judicieuse des services de santé offerts en français en Ontario - Réseau des services de santé en français de l’Est de l’Ontario (Le défi des données pertinentes pour une planification judicieuse des services de santé offerts en français en Ontario, 2013)

Les variables linguistiques : un impératif pour une planification de services de santé adaptée aux besoins des francophones. État des lieux - Réseau des services de santé en français de l’Est de l’Ontario (État des lieux, 2012)

Recommandation du Réseau. Application pratique de la Définition inclusive de francophone (DIF) - Réseau des services de santé en français de l’Est de l’Ontario (Application pratique de la Définition inclusive de francophone (DIF), 2013)

Recommandation du Réseau. Collecte des données linguistiques - Réseau des services de santé en français de l’Est de l’Ontario (2016)

Réseau recommendation. Application of the Inclusive definition of Francophone (IDF) - Réseau des services de santé en français de l’Est de l’Ontario (Application of the Inclusive definition of Francophone (IDF), 2013)

Services en français dans les CLOSM : produire des données probantes pour améliorer l’accès et la qualité. Mémoire du Réseau des services de santé en français de l’Est de l’Ontario dans le cadre de la consultation sur le renouvellement du PCLOS 2013-2018 - Réseau des services de santé en français de l’Est de l’Ontario (2016)